ANALISIS PENGARUH KEBIASAAN MAKAN MAKANAN INSTAN TERHADAP RESIKO DIABETES : MELALUI PEMBUATAN MIE KELOR PENURUN GULA DARAH - Nada, Dewi Tatum Rona Qotrun; Sya’idah , Qiftiatus; Amalia , Nisaul Azmi; Latifah, Dayang; Devi , Aulia Triana; Winarno , Amalia Novita Putri; Mol , Rebecca Jesisca; Allaudina , Amilia Wardah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Diabetes mellitus (DM) is a chronic hypoglycemic condition that can cause chronic pain to several body organs. Diabetes prevalence in Indonesia continues to increase, with 2019 RISKESDAS data showing a figure of 8.5% compared to 2013 Riskesdas, which was 6.9%. The habit of consuming sweet foods that are high in sugar contributes to an increased risk of diabetes. This research offers the innovation of Moringa noodles as a healthier alternative in the diet to lower blood sugar levels. Moringa noodles contain beneficial nutrients, including vitamins, minerals, amino acids, and antioxidant compounds. The method used in collecting data was quantitative with a questionnaire, which shows that the public has awareness of diabetes and shows interest in Moringa noodle products as a substitute for instant noodles. The results show that Moringa noodles can be an effective choice in preventing the risk of diabetes and improving healthier eating patterns.